WORKING WOMEN’S MARITAL ADJUSMENT IN TERMS OF COMMUNICATION SKILLS - Reni Fitriani; Paujiatul Arifah (Journal of Digital Media Communication, 2022)
This study aims to determine how communication skills affect working women's marital adjustment. The data collection tool used in this study is a questionnaire. The respondents in this study are 76 women who are married and working. The sampling technique used is the purposive sampling technique. At the same time, the data analysis technique used in this research is simple regression analysis. The results showed the influence of communication skills by 43.6% on marital adjustment in working women. Communication in marital relations has an important role. Women who are married and working as much as possible improve communication skills considering that time with their partner is reduced compared to women who do not work.